A Conserved EAR Motif Is Required for Avirulence and Stability of the Ralstonia solanacearum Effector PopP2 In Planta - Segonzac, C.; Newman, Toby; Choi, S.; Jayaraman, J.; Choi, D.; Jung, G.; Cho, H.; Lee, Y.; Sohn, K. (Frontiers Research Foundation, 2017)
(extract) Overall, this study reveals high conservation of the PopP2 effector in Korean R. solanacearum strains isolated from commercially cultivated tomato and pepper genotypes. Importantly, our data also indicate that the PopP2 conserved repressor motif could contribute to the effector accumulation in plant cells.